The Impact of Worksite Wellness Programs by Size of Business: A 3-Year Longitudinal Study of Participation, Health Benefits, Absenteeism, and Presenteeism. (13th September 2018) - Schwatka, Natalie V; Smith, Derek; Weitzenkamp, David; Atherly, Adam; Dally, Miranda J; Brockbank, Claire V S; Tenney, Liliana; Goetzel, Ron Z; Jinnett, Kimberly; McMillen, James; Newman, Lee S
Abstract: Objective: Worksite wellness programs (WWP) may positively impact employee health, medical expenditures, absenteeism, and presenteeism. However, there has been little research to assess the benefits of WWP in small businesses. The purpose of this study is to prospectively evaluate changes in health, absenteeism, and presenteeism for employees who participated in a WWP. Methods: We conducted an observational, 3-year cohort study of 5766 employees from 314 businesses of differing sizes. We followed two cohorts of employees, who completed at least two annual health risk assessments (HRA) between May 2010 and December 2014. Changes from baseline to the first and second follow-up periods were assessed for chronic and non-chronic health conditions, absenteeism, and presenteeism. Results: Small business employees were more likely to participate in the WWP than were employees from large businesses. Changes in chronic and non-chronic health conditions varied by size of business, with small business employees showing improvements in stress, overall health, depression, smoking status, vegetable and fruit consumption, and physical activity, and in their perceptions of job health culture. In contrast, large business employees experienced improvements in stress, vegetable consumption, and alcohol use. No changes in absenteeism or presenteeism were observed. Conclusions: Small businesses achieve higher employee participation rates and more health improvements when compared to employees from large employers. Findings suggest that small businesses may gain the most from a WWP.